University and Professional Society of Social Workers as Subjects of Personnel Training - I. M. Vorotilkina; I. V. Koroleva (Высшее образование в России)
In modern society, there is much concern about training highly qualified specialists in the field of social work. Both higher education institutions that provide this training and the professional community are interested in it. The effectiveness of the social institution activity depends on how the personnel is prepared, what competencies and the level of professionalism it possesses. Equal partnership between educational and professional communities will enable university to respond quickly to changes in the economy and the needs of the market, to train unique specialists according to professional standards. The article highlights the cooperation experience of the Department of Service, Advertising and Social Work of Sholom-Aleichem Priamursky State University with the professional community of social workers. The authors present forms and methods of the organization of social partnership as a necessary condition for training future social workers and experts in social work. Different methods of training highly qualified personnel are also shown. The authors have identified the main trajectories of interaction between the University and the professional community of social workers which are determined by the content of educational standards. They include the formation of the educational programme, the involvement of social workers in the educational process, the provision of employment, postgraduate training of personnel. The article pays special attention to the problems of profiling educational programs at universities in small regions. The authors believe that the narrow definition of educational program specialization is connected with the potential lack of demand for personnel while a shortage in specialists is maintained. The authors consider volunteering as an additional resource for the development of professional competencies in the field of social work and a channel for effective interaction between the University and the professional community.